Aspects of semilocal BPS vortex in systems with Lorentz symmetry breaking - Coronado Villalobos, C. H. [UNESP]; Hoff da Silva, J. M. [UNESP]; Hott, M. B. [UNESP]; Belich, H. (Springer, 2014)
The existence is shown of a static self-dual semilocal vortex configuration for the Maxwell-Higgs system with a Lorentz-violating CPT-even term. The dependence of the vorticity upper limit on the Lorentz-symmetry-breaking term is also investigated.